Tamoxifen Dose Escalation in Patients With Diminished CYP2D6 Activity Normalizes Endoxifen Concentrations Without Increasing Toxicity. (25th May 2016) - Hertz, Daniel L.; Deal, Allison; Ibrahim, Joseph G.; Walko, Christine M.; Weck, Karen E.; Anderson, Steven; Magrinat, Gustav; Olajide, Oludamilola; Moore, Susan; Raab, Rachel; Carrizosa, Daniel R.; Corso, Steven; et al.
Abstract : Background: Polymorphic CYP2D6 is primarily responsible for metabolic activation of tamoxifen to endoxifen. We previously reported that by increasing the daily tamoxifen dose to 40 mg/day in CYP2D6 intermediate metabolizer (IM), but not poor metabolizer (PM), patients achieve endoxifen concentrations similar to those of extensive metabolizer patients on 20 mg/day. We expanded enrollment to assess the safety of CYP2D6 genotype-guided dose escalation and investigate concentration differences between races. Methods: PM and IM breast cancer patients currently receiving tamoxifen at 20 mg/day were enrolled for genotype-guided escalation to 40 mg/day. Endoxifen was measured at baseline and after 4 months. Quality-of-life data were collected using the Functional Assessment of Cancer Therapy-Breast (FACT-B) and Breast Cancer Prevention Trial Menopausal Symptom Scale at baseline and after 4 months. Results: In 353 newly enrolled patients, genotype-guided dose escalation eliminated baseline concentration differences in IM ( p = .08), but not PM ( p = .009), patients. Endoxifen concentrations were similar in black and white patients overall ( p = .63) and within CYP2D6 phenotype groups ( p > .05). In the quality-of-life analysis of 480 patients, dose escalation did not meaningfully diminish quality of life; in fact, improvements were seen in several measures including the FACT Breast Cancer subscale ( p = .004) and limitations in range of motion ( p < .0001) in IM patients. Conclusion: Differences in endoxifen concentration during treatment can be eliminated by doubling the tamoxifen dose in IM patients, without an appreciable effect on quality of life. Validation of the association between endoxifen concentration and efficacy or prospective demonstration of improved efficacy is necessary to warrant clinical uptake of this personalized treatment strategy. Abstract : To assess the safety of tamoxifen dose escalation and investigate concentration differences between races, breast cancer patients receiving tamoxifen at 20 mg/day were enrolled for CYP2D6 genotype-guided escalation to 40 mg/day. Endoxifen was measured at baseline and after 4 months, and quality-of-life data were collected. CYP2D6 genotype-guided dose escalation eliminated baseline concentration differences in intermediate, but not poor, metabolizers, without an appreciable effect on quality of life, and endoxifen concentrations were similar in black and white patients.